Predictive factors estimation of sarcopenia secondary to cancer in the surgical patient - Damaris Aguilera Reguera; Zaily Fuentes Diaz; Orlando Bismark Rodríguez Salazar (Gaceta Médica Espirituana)
Background: Sarcopenia deteriorates physical performance, muscle strength and affects both the quality and quantity of muscle.